Applied Ergonomics For Operator Compartment Design In An EJC 88 XLP Loader - S. Thorley (The Southern African Institute of Mining and Metallurgy, 2006)
In engineering design of operator?s compartments, in underground mining equipment, ergonomics principles are often neglected or not given the full recognition they deserve. This paper defines ergonomics, applies it to machinery in an underground mining environment and describes the ergonomics analysis undertaken during the design phase of an EJC extra-low-profile mining loader. Encompassing the design of the operator?s compartment of this new loader, this paper illustrates the importance of ergonomics principles within the collective design process, ensuring that it is fully integrated into the design approach. An ultimate aim of this study is to ensure that all future designs follow this route to guarantee not only the outcome of a highly efficient, cost-effective and productive machine but that it is also takes the human factor into account, not only in maintenance but also in operation. Maximizing comfort will have the ultimate outcome of actually increasing productivity.